Augmenting excellence, promoting diversity? Preliminary design of a foundation year for the University of Cambridge. Issue 3 (5th February 2021) - Kettley, Nigel; Murphy, Colm
ABSTRACT: Undergraduate students at Cambridge come disproportionately from independent schools, high participation neighbourhoods and high socio-economic groups (SEGs). This article examines the process of designing a foundation year (FY) for Cambridge aimed at promoting SEG diversity. The transformative potential of Bourdieu's concepts of habitus, capitals and field are explored to frame the curriculum development process. Working in an intercollegiate group and drawing on international pedagogical research, we first embarked on mapping the architecture of a FY, then analysed potential students' responses to the initiative. Our survey of 304 students suggests that those from low SEGs might be encouraged to apply by a FY. They also preferred a discipline-based, not thematic, approach to developing students' academic capital. However, financial costs and concerns about 'fitting in' constituted barriers for many students. We suggest field and pedagogical transformations that are necessary to promote SEG diversity at Cambridge, rather than a FY alone.